Editorial for the Special Issue, “Quality Assay, Processing and Bio-Function of Rice Products” - Ken’ichi Ohtsubo; Carla Moita Brites; Cristina M. Rosell (Foods, 2022)
Rice is one of the most important cereals in the world alongside wheat and maize [...]